Regional free movement of persons as an opportunity in dealing with climate mobility: Great potential, difficult implementation - Kristina Korte; Emma Landmesser (Stiftung Wissenschaft und Politik (SWP), 2025)
As climate change progresses, the number of people who are being forced to leave their homes and cross borders due to environmental change is increasing. At the same time, they lack safe, orderly and regular migration pathways. Regional free movement can expand the leeway for those who are particularly affected by climate change. The African regional organisations ECOWAS (Economic Community of West African States) and IGAD (Intergovernmental Authority on Development) have both concluded agreements that could guarantee such free movement of persons. Their examples show the potential, but also the hurdles in implementing such regulations. In order to take advantage of these agreements in terms of climate mobility, German and European development and migration policy should do more to implement regional free movement. Furthermore, it is important to support the anchoring of climate aspects in the agreements. Cooperation between the European Union (EU) and individual African states should be questioned if it threatens to hinder the free movement of people in Africa through migration management and border security.
Keywords: 320; environmental change; climate change; loss and damagea; climate mobility; migration; free movement of persons; Africa; Economic Community of West African States; ECOWAS; Intergovernmental Authority on Development; IGAD; Global Compact on Migration; Nansen Initiative; Kampala Declaration; EU's external migration policy